Pengaruh Penggunaan Gadget terhadap Perkembangan Disiplin Siswa Kelas V di MIS Pesantren Dairi - Syarifah Tio Wulan R; Ramadan Lubis; Lailatun Nur Kamalia Siregar (Universitas 45 Surabaya, 2025)
This research discusses the influence of gadget use on the development of class V students' discipline at MIS Pesantren Dairi with the aim of 1) knowing the intensity of gadget use for class V students at MIS Pesantren Dairi; 2) determine the level of discipline of class V students at MIS Pesantren Dairi; 3) determine the effect of gadget use on the development of discipline in class V students at MIS Pesantren Dairi. This research uses a quantitative type of research, the approach used in this research is an ex post facto approach. Research with an ex post facto approach is used to see the influence of the independent variable on the dependent variable. The data collection technique in this research is in the form of a questionnaire distributed to students. The subjects of this research were 30 class V students at MIS Pesantren Dairi. The results of this research show that the use of gadgets influences the development of students' disciplined character in learning. The relationship between the two variables X and Y is obtained using the Pearson product moment formula with a result of 0.4711. Based on the classification table of Pearson's r correlation coefficient values, the relationship between the two variables is quite strong/quite large. From the research results, it can be concluded that the higher the use of gadgets by students, the higher the influence on the development of students' disciplinary character (negative impact). Conversely, the lower the use of gadgets by students, the lower the influence on the development of students' disciplinary character.